2007
DOI: 10.1007/s10935-007-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Eldercare Volunteers and Employees: Predicting Caregiver Experiences from Service Motives and Sense of Community

Abstract: Volunteers (n = 52) and eldercare employees (n = 160) completed measures of personal motives, sense of community, and satisfaction and stress from assisting the elderly. Caregiver satisfaction was best predicted for volunteers by feelings of reciprocal responsibility to peers. For employees, satisfaction was predicted by strong motives reflecting one's personal values, heightening self-esteem, gaining an understanding of the elderly, and a need to socialize with others. Caregiver stress for volunteers was pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…However, the results have shown that local volunteers as well as general residents who are committed to their communities were more confident in both forms of helping elderly neighbors to prevent their social isolation. Previous studies have also shown the relationships between strong SOC and being a volunteer [12,13]. Although relationships between self-efficacy and actual practices of helping elders should be confirmed in future, our results suggest the possibility that enhanced CC among community-dwelling people may facilitate the helping of elderly neighbors and could be measured as an outcome indicator of any intervention for facilitating such helping by utilizing this scale.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, the results have shown that local volunteers as well as general residents who are committed to their communities were more confident in both forms of helping elderly neighbors to prevent their social isolation. Previous studies have also shown the relationships between strong SOC and being a volunteer [12,13]. Although relationships between self-efficacy and actual practices of helping elders should be confirmed in future, our results suggest the possibility that enhanced CC among community-dwelling people may facilitate the helping of elderly neighbors and could be measured as an outcome indicator of any intervention for facilitating such helping by utilizing this scale.…”
Section: Discussionmentioning
confidence: 51%
“…Most Japanese local governments have unique informal community-based organizations or systems, composed of local volunteers (including residents in neighborhood associations, district welfare commissions, or volunteers) who support elders living in the districts with municipal community-based comprehensive care centers [11]. According to US reports [12,13], the support of elderly neighbors by local volunteers may be facilitated by the community commitment (CC) of the volunteers, defined as psychological sense of belonging and socializing in community. However, this relationship between helping elderly neighbors and CC has not been demonstrated in Japanese local volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…We can use the modification indices (Byrne 2010;Hair et al 1998) accompanied by significant theoretical explanations (Marôco 2010). Therefore, using the modification indices and the work of some authors (Ferrari et al 2007;Karr et al 2006;Millette and Gagné 2008), we considered a new relationship between motivations and management factors and some errors. The new model shows an adjustment measurement that reveals a very good adaptation of the modified structure.…”
Section: Resultsmentioning
confidence: 99%
“…The same author states that volunteer motivations influence organization management, since an organization must provide some feedback to volunteers in order to retain them. For example, if the reasons for participation in a volunteer program are related to belonging, then the management factors (e.g., recruitment and selection) should consider this motivation in order to meet volunteers expectations (Ferrari et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sense of community among neighbors improves residents' well-being [24] and increased palliative care patients' quality of life [31]. Finally, sense of community for volunteers and employees of an eldercare facility improved their experiences and decreased stress [25]. Therefore, we suggest that similar to the health benefits that sense of community provides in FtF communities, SOVC will also be related to positive health outcomes.…”
Section: Sovc and Health Outcomesmentioning
confidence: 93%